Perspective of Students on the Use of Recreational Activities in Virtual Environments in the Sustainable Production Course, UNED (Revista Electrónica Calidad en la Educación Superior, 2020)
The use of recreational activities as learning tools within the learning process was implemented in three subjects during 2018, with the aim of getting insight about the perception of students on the use of these activities as teaching and learning strategies in the virtual environments.  This methodology is being used for the first time in the Sustainable Production course and in the Natural Resource Management program. The use of these activities provided a fresh focus on the student’s way of learning. It also generated a feeling of satisfaction when participating, and when getting the highest score, or, otherwise, insight on what contents they need to study more.  From the observed group, 83% of the students found it entertaining. However, it was tense for a group of students: the first time the bachelor’s degree students faced this type of activity, they felt uncomfortable, though the next four months they faced other similar activities and their acceptance was much better.
Keywords: Virtual environments, recreational activities, course, self-learning and self-evaluation